Phage as a Template to Grow Bone Mineral Nanocrystals - Cao, Binrui (Methods Mol Biol, 2014)
Phage display is a biotechnique that fuses functional peptides on the outer surface of filamentous phage by inserting DNA encoding the peptides into the genes of its coat proteins. The resultant peptide-displayed phage particles have been widely used as biotemplates for the synthesis of functional hybrid nanomaterials. Here, we describe the bioengineering of M13 filamentous phage to surface-display bone mineral (hydroxyapatite (HAP))-nucleating peptides derived from dentin matrix protein-1 and using the engineered phage as a biotemplate to grow HAP nanocrystals.